2021
DOI: 10.3389/fmicb.2021.667833
|View full text |Cite
|
Sign up to set email alerts
|

Cuminum cyminum L. Essential Oil: A Promising Antibacterial and Antivirulence Agent Against Multidrug-Resistant Staphylococcus aureus

Abstract: Cuminum cyminum L. (cumin) is valued for its aromatic and medicinal properties. There are several reports of antibacterial activity of C. cyminum essential oil (CcEO). Accordingly, the present study was conducted to investigate the mechanism(s) of action of the CcEO against multidrug-resistant (MDR) Staphylococcus aureus. Therefore, 10 S. aureus MDR isolates, obtained from different sources, were selected based on the antibiotic susceptibility patterns and the Clinical and Laboratory Standards Institute defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…The inhibition of the BDMC on the biofilm formation of S. aureus DPS-1, DPS-2, and ATCC 33591 was established in a crystal violet biofilm assay using a previously described protocol [36]. To each well of 96-well microtiter plates, 100 µL of overnight culture (0.5 MacFarland bacterial culture) was added and treated with sub-concentrations of BDMC.…”
Section: Crystal Violet Biofilm Assaymentioning
confidence: 99%
“…The inhibition of the BDMC on the biofilm formation of S. aureus DPS-1, DPS-2, and ATCC 33591 was established in a crystal violet biofilm assay using a previously described protocol [36]. To each well of 96-well microtiter plates, 100 µL of overnight culture (0.5 MacFarland bacterial culture) was added and treated with sub-concentrations of BDMC.…”
Section: Crystal Violet Biofilm Assaymentioning
confidence: 99%
“…This variation could be ascribed to the genetic differences in both species [ 24 ], and the environmental and climatic conditions have also been reported to affect the composition of the EO [ 23 , 25 , 26 , 27 ]. Cuminic aldehyde is basically the main compound of Cuminum cyminum, with a concentration of 22.4–41.5% [ 28 , 29 , 30 ]. On the other hand, p -cymen-7-ol was described as a major compound in the EOs of several plants, for instance, Curcuma cf.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study by de Sousa, et al [ 50 ] indicated that the combination of carvacrol and 1,8-cineole maximizes the inhibitory activity against bacterial strains associated with vegetable processing. In addition, cuminic aldehyde has been reported to have antibacterial effects [ 29 , 30 ]. In contrast to our results, the EO of C. cyminum , rich with cuminic aldehyde, did not show antibacterial activity against Pseudomonas species [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quorum-sensing-mediated inter-bacterial communication has been recognized as an important signaling communication mode in bacterial flora ( Mukherjee and Bassler 2019b ). Numerous studies have shown that bicyclic terpenoids have significant antibacterial and anti-biofilm activities ( Sharifi, Mohammadzadeh et al, 2021 ). 1,8-cineole is the active ingredient in the essential oil extracted from most camphoraceous plants.…”
Section: Discussionmentioning
confidence: 99%